Stability of cadmium-induced renal injury biomarkers in adult residents with long-term environmental cadmium exposure: a 13-month follow up survey - Mei WANG; Jun YAN; Chen-yang ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo investigate the stability of cadmium-induced renal injury biomarkers in community adults with low environmental exposure. MethodsThe participants of the survey were 80 permanent residents aged 40 - 69 years living in local areas at least 10 years (63 in an area with relatively heavy environmental cadmium pollution and 17 in an area with similar social and economic development to those of the contaminated area but with low environmental cadmium pollution) in Gansu province. Peripheral blood and morning urine samples of the participants were collected three times in November 2019, November 2020 and December 2020, for detections of blood cadmium, urinary cadmium, urinary β2-microglobulin (Uβ2-MG), urinary N-acetyl-β-D-glucosaminidase (UNAG), urinary retinol binding protein (URBP), urinary metallothionein (UMT) and urinary micro-albumin (UALB), respectively. Relevant information of the participants were collected simultaneously with questionnaire interviews. Descriptive statistics with variance analysis and Chi-square test were performed on the data collected. ResultsThe main effects of time on blood cadmium, UALB, UMT and URBP were not statistically significant (all P > 0.05). The main effects of time on urinary cadmium, UNAG and Uβ2-MG were statistically significant (all P < 0.001). Pairwise comparison showed that there were no significant differences in blood cadmium, UALB, UMT and URBP levels among detections at the three time points (all P > 0.05); but the levels of urinary cadmium in the second and third detection were significantly higher than that in the first detection (both P < 0.001); the level of urinary cadmium in the third detection was significantly higher than that in the second detection (P < 0.01); the UNAG level of the second detection was significantly higher than that of the first detection and the third detection (both P < 0.001). There was no significant difference in UNAG level between the first test and the third test (P > 0.05). The Uβ2-MG level in the third detection was significantly higher than that in the first and the second detection (both P < 0.001). There was no significant difference in Uβ2-MG level between the first and second detection (P > 0.05). ConclusionBlood cadmium, UALB, UMT and URBP are less affected by time effect and of good stability; while urine cadmium, UNAG and Uβ2-MG are more affected by time effect and of poor stability.